A Combined Pharmacometrics Analysis of Biomarker Distribution Under Treatment With Standard- or Low-Dose Rivaroxaban in Real-World Chinese Patients With Nonvalvular Atrial Fibrillation - Zhao, Nan; Liu, Zhiyan; Xie, Qiufen; Wang, Zhe; Sun, Zhongyi; Xiang, Qian; Cui, Yimin (Frontiers in Pharmacology, 2022)
Background: The rivaroxaban dose regimen for patients with nonvalvular atrial fibrillation (NVAF) is complex in Asia. Given the high interindividual variability and the risk of bleeding caused by rivaroxaban in Asians, the influencing factors and the relationship between outlier biomarkers and bleeding events need exploration. Methods: The integrated pharmacokinetics (PK)/pharmacodynamics (PD) models were characterized based on rich PK/PD data from 304 healthy volunteers and sparse PD [anti-factor Xa activity (anti-Xa) and prothrombin (PT)] data from 223 patients with NVAF. The correlations between PD biomarkers and clinically relevant bleedings in 1 year were explored. The final integrated PK/PD model was used to evaluate the influence of dosage and individual covariates on PD parameters. Results: A two-compartment, linear model with sequential zero-order and first-order absorption was adopted. The dose-specific relative bioavailability (F1), diet status, creatinine clearance, and body mass index (BMI) improved the model fit. The apparent systemic clearance was 7.39 L/h, and the central and peripheral volumes were 10.9 and 50.9 L, respectively. The linear direct-effects model with shape factor plus the additive (and/or proportional) error model described the correlation between anti-Xa/PT and plasma concentration. Bodyweight, total cholesterol (TCHO), and diet status were selected as the covariates of the anti-Xa/PT model. Anti-Xa was more sensitive to the increase in rivaroxaban exposure compared with PT. An elevated bleeding tendency was seen with higher peak anti-Xa and PT. For a typical Chinese patient, the peak anti-Xa value (median (5%–95% PI)) of 20 and 15 mg were 309 ng/ml (139–597 ng/ml) and 296 ng/ml (138–604 ng/ml), both median values were within the expected range. For patients with CrCL 30–49 ml/min, the median peak anti-Xa with recommended 10 mg other than 15 mg were within the expected range. Conclusion: Fixed doses of rivaroxaban could be prescribed for patients with NVAF without adjustment for bodyweight, BMI, and TCHO. Randomized studies should be performed to evaluate the efficacy and safety of low-dose rivaroxaban in Chinese patients with NVAF.